Digital History of Law: Principles of Methodology - S. V. Lonskaya (Journal of Digital Technologies and Law, 2024)
Objective: to theoretically substantiate the basic principles of methodology of a new interdisciplinary area of socio-humanities – the digital history of law; to demonstrate the heuristic potential of digital technologies in legal historical sciences.Methods: the study is based on systemic, formal-logical, and comparative general scientific methods.Results: it is concluded that the methodology of the digital history of law is based, first of all, on the source-centric approach, which considers a source as a macro-object of humanitarian and social sciences, through which information exchange takes place (O.M. Medushevskaya’s concept of cognitive history). Secondly, it is based on the combination of traditional methods of legal history with digital techniques and technologies and methods based on them – within a research program of historical-legal (historical-juridical) source studies. The article attempts to summarize the existing digital technologies and techniques, as well as methods based on them, as applied to legal historical sciences; their heuristic potential is shown in case studies.Scientific novelty: for the first time in the Russian legal history science, the author substantiates the methodology of the digital history of law as an interdisciplinary field that studies the past of state and law using digital information and communication technologies and tools.Practical significance: under the shifts in socio-humanities (digital, linguistic, visual ones, etc.), which have become relevant in recent years, and the development of the digital type of social communication, methodological approaches to obtaining new knowledge are changing, new interdisciplinary branches of scientific knowledge are emerging, as well as new requirements for the qualification of researchers. The ongoing changes affect legal historical sciences: digital history of law is formed as an interdisciplinary area within digital humanities, at the confluence of history, legal science, and information science. The understanding and application of digital technologies and the scientific cognition methods based on them in legal historical research open up new opportunities for legal historians in determining the directions of their scientific research and obtaining new scientific results. This ultimately expands our understanding of historical and legal facts, phenomena and processes.